1996
DOI: 10.1016/s0168-8278(96)80323-0
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant hepatic failure in pregnant women: acute fatty liver or acute viral hepatitis?

Abstract: We conclude that hepatitis E is the usual cause of acute liver failure in our pregnant women and that clinical and laboratory features do not permit accurate distinction between acute HEV infection and acute fatty liver of pregnancy. The prognosis in patients with acute HEV infection is much better than in other groups with severe liver failure (mortality 16% vs 68%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(70 citation statements)
references
References 20 publications
3
64
0
3
Order By: Relevance
“…Various reports evaluating etiological spectrum in individuals with acute hepatitis during both epidemic and sporadic settings indicate three distinct observations in India: 1) HEV is the commonest cause of AVH in both sporadic and epidemic settings [3][4][5][6][7][8][9][10] 2) The frequency of HEV as the cause of AVH is significantly higher among pregnant females than in non-pregnant females and males 24,25,[42][43][44][45][46][47] 3) The frequency of ALF is significantly higher in pregnant females than in non-pregnant females and males with HEV infection. 7,24,25,43,45 Tables 3 and 4 7,11,12,[42][43][44][45][46][48][49][50] highlight the sporadic and epidemic studies of HEV induced AVH/ALF reported in pregnant females.…”
Section: Pregnant Females Are More Susceptible To Contract Hepatitis mentioning
confidence: 99%
See 1 more Smart Citation
“…Various reports evaluating etiological spectrum in individuals with acute hepatitis during both epidemic and sporadic settings indicate three distinct observations in India: 1) HEV is the commonest cause of AVH in both sporadic and epidemic settings [3][4][5][6][7][8][9][10] 2) The frequency of HEV as the cause of AVH is significantly higher among pregnant females than in non-pregnant females and males 24,25,[42][43][44][45][46][47] 3) The frequency of ALF is significantly higher in pregnant females than in non-pregnant females and males with HEV infection. 7,24,25,43,45 Tables 3 and 4 7,11,12,[42][43][44][45][46][48][49][50] highlight the sporadic and epidemic studies of HEV induced AVH/ALF reported in pregnant females.…”
Section: Pregnant Females Are More Susceptible To Contract Hepatitis mentioning
confidence: 99%
“…7,24,25,43,45 Tables 3 and 4 7,11,12,[42][43][44][45][46][48][49][50] highlight the sporadic and epidemic studies of HEV induced AVH/ALF reported in pregnant females.…”
Section: Pregnant Females Are More Susceptible To Contract Hepatitis mentioning
confidence: 99%
“…The diagnosis of acute liver failure is made clinically on the basis of physical examination findings such as altered mental status and supportive laboratory results like prolonged prothrombin time [3]. The most commonly identified causes of acute liver failure include medications and idiosyncratic drug toxicity, initial presentation of autoimmune hepatitis and viral infections [4][5][6][7] also we should keep in mind other possibilities for example Eclampsia, Fatty liver of pregnancy, Hepatic ischemia, Malignant infiltration, Toxins and/or Wilson disease [4,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis E is primarily transmitted through the fecal-oral route, with an incubation period of about 15 to 60 days. The mortality rate is generally low (about 1%); however, it can reach up to 15 to 25% among infected pregnant women (7,23,24 …”
mentioning
confidence: 99%
“…Hepatitis E is primarily transmitted through the fecal-oral route, with an incubation period of about 15 to 60 days. The mortality rate is generally low (about 1%); however, it can reach up to 15 to 25% among infected pregnant women (7,23,24). HEV is a public health concern in many developing countries; however, sporadic cases of acute hepatitis E have also been reported in many industrialized countries, including the United States (3, 13-14, 17, 20, 22, 26, 31, 33, 37).…”
mentioning
confidence: 99%